The role of highly dispersed silica nanoparticles in the realization of the effects of granulosa on the maturation and fertilization competence of Sus scrofa domesticus oocytes - T. I. Kuzmina; I. V. Chistyakova; A. O. Prituzhalova; D. N. Tatarskaya (Вавиловский журнал генетики и селекции)
Reproductive technologies are some of the key directions in the context of the need to preserve and select highly productive farmed animals in terms of economically useful traits. Improvements of the existing models of the in vitro oocyte maturation system help to solve the problem of low yield of porcine embryos at the final stages of preimplantation development. In the present study, a model of culture medium for gametes (NCSU-23 with 10 % homologous follicular fluid, 10 IU hCG and 10 IU eCG) modernized by the addition of 1·106 granulosa cells (GCs) per ml and 0.001 % of highly dispersed silica nanoparticles (HDSn) is proposed for use in the IVM and IVF technology of donor porcine oocytes. Analysis of the oocyte chromatin status by the Tarkowsky method and assessment of the level of destructive changes in chromatin (apoptosis, pyknosis) revealed a significant percentage increase in matured oocytes and a decrease in the proportion of granulosa cells with degenerated chromatin when using the original culture system. The positive effects of a joint addition of GCs and HDSn to the maturation system have made it possible to increase the indicators of the meiotic maturation and fertilization of oocytes. Optimal results of developmental competence of oocytes were achieved with the joint use of GCs and HDSn in the maturation system (the proportion of matured cells reached 89 %, the level of oocytes with chromosome degeneration was 12 %, 39 % of embryos reached the final stage of preimplantation development). The positive effect of HDSn on oocyte fertilization was accompanied by an abrupt decrease in destructive processes in GCs during culture in the presence of HDSn. The level of somatic cells with pyknotic nuclei was 32 % and the level of apoptosis (TUNEL-test), 21 %, compared with the control (43 and 31 %, p <0.01, respectively). Thus, a high efficiency of the porcine oocyte maturation system in the joint culture of gametes with GCs and HDSn was revealed. It makes it possible to recommend a model of this culture medium at the IVM of female gametes of Sus scrofa domesticus for improving the quality of donor oocytes used in cell and genetic engineering.